<em>x = - 2</em>
- <em>Step-by-step explanation:</em>
<em>Hi there ! </em>
<em>5x - 6 = - 16</em>
<em>5x = - 16 + 6</em>
<em>5x = - ( 16 - 6)</em>
<em>5x = - 10</em>
<em>x = - 10 : 2</em>
<em>x = - 2</em>
<em>Good luck ! </em>
Answer:
28
Step-by-step explanation:
sry if I'm wrong although I used calculator
Answer:x=24
Step-by-step explanation:x/2-8=4
Add 8 to both sides
x/2=12
Multiply each side by 2
x=24
Answer:
The error made is that the graph of
is a vertical translation up by 3, instead of down.
Step-by-step explanation:
Exponential functions, when they are graphed, use the function
.
In the equation, k expresses how much the graph shifts vertically. In this case, the function shifts vertically up by 3 from the parent function,
. So, the translation is actually 3 units up compared to the graph of
.
Hope this helps and have an amazing day!! ❤
Answer:
a) next one is previous one -3
b) next one is 3 times previous one